2007
DOI: 10.1017/s0033822200042855
|View full text |Cite
|
Sign up to set email alerts
|

Do Riparian Plants Fix CO2 Lost by Evasion from Surface Waters? An Investigation Using Carbon Isotopes

Abstract: ABSTRACT. Rivers and streams in many parts of the world contain high concentrations of dissolved carbon dioxide, which is lost to the atmosphere by evasion (outgassing). Recent methodological advances now enable the carbon isotopic composition of this evaded CO 2 to be measured directly, with early results from peatland streams showing it to be depleted in 13 C relative to the atmosphere. The first direct measurements of the radiocarbon age of evaded CO 2 for a stream draining a peatland site in the United Kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Although streams draining UK peatlands are widely regarded as acidic, organic‐rich systems, they clearly provide a pathway for the potential release of old CO 2 to the atmosphere derived from deep carbonate weathering. Recent work has shown that this old CO 2 can be assimilated by plants growing in the vicinity of peatlands streams [ Garnett and Billett , 2007]. Whilst the presence of old evaded CO 2 derived from peat decomposition cannot be firmly established in this study, it clearly has the potential to contribute to the evasion loss pathway.…”
Section: Resultsmentioning
confidence: 69%
“…Although streams draining UK peatlands are widely regarded as acidic, organic‐rich systems, they clearly provide a pathway for the potential release of old CO 2 to the atmosphere derived from deep carbonate weathering. Recent work has shown that this old CO 2 can be assimilated by plants growing in the vicinity of peatlands streams [ Garnett and Billett , 2007]. Whilst the presence of old evaded CO 2 derived from peat decomposition cannot be firmly established in this study, it clearly has the potential to contribute to the evasion loss pathway.…”
Section: Resultsmentioning
confidence: 69%
“…Terrestrial plant samples were measured for δ 15 N, and the Δ 14 C of FTOM was assumed to match the value of atmospheric CO 2(Garnett & Billett, 2007;Randerson, Enting, Schuur, Caldeira, & Fung, 2002), which was 40 ± 3‰ (zero years old) in the Northern Hemisphere in 2010(Levin, Kromer, & Hammer, 2013). Terrestrial plant samples were measured for δ 15 N, and the Δ 14 C of FTOM was assumed to match the value of atmospheric CO 2(Garnett & Billett, 2007;Randerson, Enting, Schuur, Caldeira, & Fung, 2002), which was 40 ± 3‰ (zero years old) in the Northern Hemisphere in 2010(Levin, Kromer, & Hammer, 2013).…”
mentioning
confidence: 99%
“…Since, the magmatic CO 2 is 14 C-free, this results of a 14 C dilution in plants of the surrounding areas (Cook et al, 2001;Pasquier-Cardin et al, 1999). Garnett and Billett (2007) follow a similar approach in Tyrrhenian Sea. 14 C activity measurements can then be used as a way to track changes in volcanic activity.…”
Section: Volcanic Areamentioning
confidence: 77%